ANALYSIS OF INTERNATIONAL TRADE POLICY REGARDING INDONESIA’S EXPORTS OF PROCESSED COCOA POWDER TO INDIA FOR THE PERIOD 2015–2025 - Desti Purnama; Rizal Budi Santoso (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the role of cocoa bean export duty policy in promoting the downstream development of the cocoa industry and increasing Indonesia’s cocoa powder exports to India during the 2015–2025 period. The study employed a descriptive qualitative method using document analysis from Trade Map, UN Comtrade, BPS, and various scientific publications. The findings indicate that the export duty policy has successfully reduced raw cocoa bean exports and encouraged the growth of the domestic cocoa processing industry. The increased availability of raw materials has also supported cocoa powder exports to India as one of the potential export markets. However, the downstreaming process still challenges, including low cocoa productivity and limited domestic raw material supply